A simulation/optimisation approach to support the resource allocation in service firms. (2018) - Romano, E.; Iuliano, D.
Simulation modelling is a useful tool to produce a quantitative decision support in different application areas. It is extremely useful for predicting the constant changes that take place in a highly dynamic context such as that of services. This paper examines the widespread problem of extended waiting times for health services, considering a regional private hospital, through building and validation of a computer simulation model. Using Arena simulation software for modelling, analysis, visualisation and optimisation of the patient flow within the service structure considered. The model will be utilised to simulate the impacts of different proposed operating strategies on waiting time and throughput rate for patients. The objective is to identify those strategies which lead to higher efficiency for the hospital's resources without decreasing in the quality for the patient care.